Hydropower Potential of Montenegro - Ratko, Mitrović (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
As the existing total hydropower potential of Montenegro is outdated, an attempt is made to re estimate the potential and also to assess the possibility of the utilization of the total hydropower potential in Montenegro in newly created conditions and opportunities. The methodology used is based on energy potential for each watercourse individually taking account of the total amount of water from precipitation and transit waters at the territory of Montenegro. This paper for the first time integrally analyses hydropower potential in both gauged and ungauged major watercourses and their tributaries. It provides insight into the total hydropower potential and technically exploitable hydropower potential for both Run-of-River and storage projects, which may serve as a good basis for strategic planning of exploitation of this resource. It bears specific importance since hydropower exploitation of the remaining 82% of this potential is expected in the near future. The technically exploitable hydropower potential is assessed as 9840 GWh in a year. DOI: http://dx.doi.org/10.3126/hn.v9i0.7076 Hydro Nepal Vol.9 July 2011 63-68